Effect of blood group types on live body weight of unimproved Awassi sheep - AL-Khuzai, Hamza Mizail; Khazraji, Wasan Jasim AL- (Sulaimani Journal for Pure and Applied Sciences, 2018)
The current study was conducted to determine the effect of blood groups on live body weight from birth to 9thmonth of age in Awassi sheep. Two hundred and twenty five ewes and 110 rams of unimproved Awassi sheep reared in private farm at AL-Dewanya province (middle of Iraq) during the breeding season of 2015-2016 were used. Results revealed a significant differences (P˂0.01)according to the blood groups for both rams and ewes. The highest number of rams had D blood group observed as compared with the lowest number had R blood group, namely44 (40%) and13 heads (11.82%) respectively. The highest number of ewes had D blood group noticed as compared with the lowest number had R blood group, namely91(40.44%) and 27 heads (12.00%) respectively. Moreover, the results showed absence of other blood groups like C, M and X in both rams and ewes in the current study. Significant effect(P˂0.05) of blood groups on ram’ s live body weight was also investigated, being highest at birth, weaning, sixth and ninth months of age with blood group B namely, 3.88, 20.53, 25.83 and 26.69 kg respectively. Non significant effect of blood group on birth weight in ewes while blood group B had the highest weight (P˂0.05) for other ages namely 19.95, 23.80 and 25.99 kg respectively.
Keywords: Awassi sheep Blood groups; Body weight,